Electrical characterization of different high-k dielectrics with tungsten silicide in vertical double gate nmos structure - Kaharudin K.E.; Salehuddin F.; Soin N.; Zain A.S.M.; Aziz M.N.I.A.; Ahmad I. (Asian Research Publishing Network, 2023)
The limitation of Poly-Si/ SiO2 devices in producing a greater value of drive current (ION) has become a major issue, especially for very small scale devices. It is believed that the problem may be resolved by introducing metalgate/ high-k dielectrics to replace traditional Poly-Si/SiO2 technology. This paper presents the performance analysis of several different high-k dielectrics technology with tungsten silicide (WSix) as a metal-gate in ultrathin pillar vertical double-gate (DG) NMOS architecture. The device was virtually fabricated by using an ATHENA module of Silvaco TCAD tools. At the same time, the device characterization was carried out using an ATLAS module of Silvaco TCAD tools. The dielectric materials used for the simulation are known as Al2O3, HfO2, TiO2 and ZrO2. Analysis of the results revealed that the WSix/TiO2 device has superior electrical characteristics compared to others. The significant improvement was observed in terms of the drive current (ION) where the WSix/TiO2 device produced 2.845.2 ?A/?m at 0.205 V of threshold voltage (VTH). This ION value exceeds the minimum requirement predicted by the International Technology Roadmap Semiconductor (ITRS) 2013 for high performance (HP) multi-gate (MG) technology. 2006-2016 Asian Research Publishing Network (ARPN).